2007
DOI: 10.1111/j.1467-9280.2007.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Priming in Comprehension

Abstract: Syntactic priming is the facilitation of processing that occurs when a sentence has the same syntactic form as a preceding sentence. Such priming effects have been less consistently demonstrated in comprehension than in production, and those that have been reported have depended on the repetition of verbs across sentences. In an event-related potential experiment, subjects read target sentences containing reduced-relative clauses. Each was preceded by a sentence that contained the same verb and either a reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 39 publications
12
65
1
Order By: Relevance
“…To date, published studies indicate syntactic priming during interpretation for sentences containing reduced relative clauses (Ledoux et al, 2007; Tooley et al, 2009; Traxler, 2008b; Traxler & Tooley, 2008), prepositional object and double-object datives (Arai et al, 2007; Carminati & van Gompel, 2008; Thothathiri & Snedeker, 2008a, 2008b), modifier-goal ambiguities (Traxler, 2008a), coordinate noun-phrases within sentences (Frazier et al, 2000; Scheepers & Crocker, 2004; Sturt et al, 2010), object-complement ambiguities (Trueswell & Kim, 1998), and “high-low” attachment ambiguities (Boudewyn et al, in press). Repetition of syntactic form has also been shown to influence repetition suppression effects in an fMRI study of passive voice sentences, which extended to conditions where the prime was given in one language (e.g.…”
Section: Studies Of Syntactic Priming In Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, published studies indicate syntactic priming during interpretation for sentences containing reduced relative clauses (Ledoux et al, 2007; Tooley et al, 2009; Traxler, 2008b; Traxler & Tooley, 2008), prepositional object and double-object datives (Arai et al, 2007; Carminati & van Gompel, 2008; Thothathiri & Snedeker, 2008a, 2008b), modifier-goal ambiguities (Traxler, 2008a), coordinate noun-phrases within sentences (Frazier et al, 2000; Scheepers & Crocker, 2004; Sturt et al, 2010), object-complement ambiguities (Trueswell & Kim, 1998), and “high-low” attachment ambiguities (Boudewyn et al, in press). Repetition of syntactic form has also been shown to influence repetition suppression effects in an fMRI study of passive voice sentences, which extended to conditions where the prime was given in one language (e.g.…”
Section: Studies Of Syntactic Priming In Comprehensionmentioning
confidence: 99%
“… Syntactic priming occurs when structural information from one sentence influences processing of a subsequently encountered sentence (Bock, 1986; Ledoux et al, 2007). This article reports two eye-tracking experiments investigating the effects of a prime sentence on the processing of a target sentence that shared aspects of syntactic form.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, after reading a sentence with a reduced relative clause (e.g. The man watched by the woman was tall and handsome ), subsequent reduced-relative sentences are read faster (Traxler & Tooley, 2008) and with less disruption (reflected in smaller P600s in measures of event-related potentials; Ledoux, Traxler, & Swaab, 2007; Tooley et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent studies have shown that the comprehension of a syntactic form is indeed facilitated by the recent exposure to a similar syntactic form, and there are a number of ways in which syntactic priming can affect the comprehension of a subsequent target stimulus. Priming can ease the recovery from syntactic garden paths (Branigan, Pickering, Liversedge, Stewart, & Urbach, 1995; Ledoux, Traxler, & Swaab, 2007;Traxler, 2008); it can also affect the final interpretation of a globally ambiguous sentence (Branigan, Pickering, & McLean, 2005); and it can modulate expectation levels for upcoming constituents, as measured by eye-movements during scene viewing (Arai, Gompel, & Scheepers, 2007; Thothathiri & Snedeker, 2008).…”
Section: Introductionmentioning
confidence: 99%